2008
DOI: 10.1159/000173719
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Metachronous Gastric Cancer in High-Risk Patients after Successful <i>Helicobacter pylori</i> Eradication

Abstract: Background:Helicobacter pylori eradication following endoscopic mucosal resection of early gastric cancer reduces the risk of metachronous gastric cancer. Aim: To identify subgroups of differing cancer risk after endoscopic mucosal resection of early gastric cancer. Methods: Histological assessment of antral and corpus tissue was done by the updated Sydney Classification and serum pepsinogen I and II levels were measured using ELISA kits. Infected patients were treated with a 7-day regimen consisting of amoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 41 publications
4
65
2
1
Order By: Relevance
“…Previously, a few studies suggested risk factors for metachronous cancer, such as H. pylori infection [17], chronic atrophic gastritis [13,14,16], and undifferentiated histologic appearance [15]. However, there have been many limitations in terms of relatively small numbers of patients, lack of evaluation for premalignant dysplastic lesions, and adjustment with multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a few studies suggested risk factors for metachronous cancer, such as H. pylori infection [17], chronic atrophic gastritis [13,14,16], and undifferentiated histologic appearance [15]. However, there have been many limitations in terms of relatively small numbers of patients, lack of evaluation for premalignant dysplastic lesions, and adjustment with multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, metachronous gastric cancer tended to develop in the same third of the stomach as the primary lesion with similar macroscopic and differentiated type [12]. Another two studies showed that atrophy in the background gastric mucosa was associated with the development of metachronous gastric cancer [13,14]. In another study, undifferentiated histologic appearance of the primary lesion was related to the occurrence of synchronous or metachronous gastric cancer [15].…”
Section: Introductionmentioning
confidence: 96%
“…However, the development of metachronous gastric cancer (MGC), owing to the preservation of the entire stomach after endoscopic resection, remains a possibility [8][9][10]. A previous multicenter prospective randomized study performed in Japan showed that eradication of Helicobacter pylori reduced the incidence of MGC after endoscopic resection for early gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…A previous multicenter prospective randomized study performed in Japan showed that eradication of Helicobacter pylori reduced the incidence of MGC after endoscopic resection for early gastric cancer [11]. However, MGC sometimes develops even after successful H. pylori eradication, with an annual incidence of 0.8-4.1 % [9][10][11][12][13][14][15]. In most previous studies, only incidences of MGC within a 3-year median follow-up period were reported, and a study with a longer follow-up period is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation